Analysis of Single Frequency Network (SFN) Under Delay Time - Ruckveratham, Bandit; Promwo, Sathaporn (International Journal of Engineering and Technology, 2018)
Single Frequency Network (SFN) is the key advantage option of Digital television terrestrial broadcast. Wherewith, it makes use of the frequency is worthwhile for planning the network. Using SFN makes it possible to cover the broadcast area with just one frequency. In this research, we present the effect of SFN, regardless of the SFN gain, Modulation Error Ratio (MER), Noise margin, by the effect of the signal delay within the guard interval (GI). The finding of this research is that show the SFN gain is higher during the echo delay that is    0 microseconds away. However, on the other hand, MER has declined. The results from this research are useful for designing and improving the SFN network of the digital television transmission.